2015
DOI: 10.1007/s00420-015-1068-4
|View full text |Cite
|
Sign up to set email alerts
|

Fire fit: assessing comprehensive fitness and injury risk in the fire service

Abstract: This 5-year analysis of clinical occupational health assessments enabled the development of a relevant metric for relating comprehensive fitness with the risk of injury. Results were consistent with previous studies focused on cardiorespiratory fitness, but also less susceptible to inter-individual variability of discrete measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 21 publications
3
54
1
1
Order By: Relevance
“…The RM process identified that while on-shift exercise was necessary for maintaining fitness, it lacked the necessary structure, guidance and management to ensure safe performance. Two retrospective cohort analyses on the current study’s population (Poplin et al, 2014 ; Poplin et al, 2016 ) found that over a five year span, “fit” and “less fit” commissioned FD employees were found to have an increased likelihood for injury than their “most fit” peers. However, PE, if performed improperly, frequently results in injury.…”
Section: Discussionmentioning
confidence: 71%
“…The RM process identified that while on-shift exercise was necessary for maintaining fitness, it lacked the necessary structure, guidance and management to ensure safe performance. Two retrospective cohort analyses on the current study’s population (Poplin et al, 2014 ; Poplin et al, 2016 ) found that over a five year span, “fit” and “less fit” commissioned FD employees were found to have an increased likelihood for injury than their “most fit” peers. However, PE, if performed improperly, frequently results in injury.…”
Section: Discussionmentioning
confidence: 71%
“…Studies included 10 cohort and one matched case‐control design with study follow‐up periods ranging to 12 weeks to 9 years. Of the included studies that reported incidence of injury, the cumulative incidence rates per 100 workers ranged between 5.3 and 101.8 injuries per year . Injuries were ascertained in various ways including self‐report, workers’ compensation claims, and surveillance records.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies had lower scores because self‐reports were used as an assessment of outcome rather than data linkage or independent blind assessment . Three studies scored two points for comparability as multiple confounders were controlled for, whereas three studies scored zero points as no confounders were controlled for . The single case control study was evaluated regarding selection, comparability, and exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations